Sugarcane Production and Productivity growth scenario in India - Sharma, A K; Pathak, A D (Indian Farming, 2017)
Front line demonstrations of potential technologies need to be carried out in those districts in all major cane growing states where the average yields of the district are high compared to the FLD yield levels. Those areas having less yield levels compared to state averages need to be identified for addressing resource constraints by giving emphasis on microirrigation, healthy seed, nutrients and greater input of extension, while areas having higher cane yields be identified for infusing greater inputs of technological advancements through demonstrations and other innovative extension methods.